The Security of Domestic Environment in Islam | الأمن في المحيط الأسري في الإسلام - Ahmaddin Ahmad Tohar (Al-Zahra : Journal for Islamic and Arabic Studies, 2018)
Family plays an important role in life because every human, including Muslim, certainly departs from a family. A family is a small community built from a marriage, and it is the beginning of building Islamic household containing harmony, love and mercy. The ideal family that are filled with security, peace and peace of mind. In Islam, the family is part of the Islamic community in which someone learns Islam from childhood. In the family, principles of Islamic values are delivered for the first time. Parents and children, also, will guard each other against immoral acts. Having a harmonious family that is accordance with the Islamic values is the dream of every Muslim and in order to realize it, Muslim should obey all the rules of Allah Almighty.